Contact and head acceleration characteristics of a female rugby union team during an international tournament - Menzies, F.; Scantlebury, S.; Jones, B.; Boyd, A.; Pugh, D.; Robson, J.; Ramirez, C. (BASES Conference 2024, 2024)
Rugby union participation imposes substantial stressors and demands upon players, including locomotor demands and contact exposure. Contact and head acceleration event (HAE) exposure have been studied in match-play but have yet to be reported in female rugby union training. Quantifying contact and HAE exposure in both match-play and training is required to improve load management, injury prevention and other player welfare strategies. The aim of this study was to report contact and HAE exposure characteristics of an international female rugby union team, across a three-week international tournament, encompassing match and training contexts. With institutional ethical approval, contact and HAE exposure of 28 female rugby union players were assessed using video analysis and instrumented mouthguards. Three matches and 16 train ing sessions were coded using consensus operational definitions, and synchronised with instrumented mouthguard data, enabling calculation of HAE incidence and propensity by skill type. Effect sizes and 95% confidence intervals (ES+95%CI) were calculated to quantify the magnitude of differences. Training activity accounted for 76-85% of weekly contact volume. There was a large difference in forwards` and backs` contact volumes during matches (45.5+27.1 vs. 20.8+12.6 con tacts per match, ES = 1.12+0.55) and full contact training (26.9 +7.4 vs. 11.6+2.7 contacts per match week, ES=2.64+0.63), whereas the effect size for contact volume in controlled contacttraining was small (80.5+28.4 vs. 74.6+22.1 contacts per match week, ES=0.23+0.46). HAE propensity was greater in matches than training for all peak linear and angular acceleration thresh olds. The tackle event accounted for 82% and 71% of HAEs >25g in matches and training respectively. Contact exposure of training should be routinely monitored, considering the sub stantial contribution of training to weekly cumulative exposure. The inter-individual variation observed in HAE propensity sug gests that load management should be considered on an indi vidual basis. Strategies to reduce HAE burden should be focussed on the tackle area, given that the majority of HAEs are attributed to the ball carrier and tackler